Impact of Window Computed Tomography (CT) Parameters on Measurement of Inflammatory Changes in Paranasal Sinuses - Cebula, Maciej; Danielak-Nowak, Monika; Modlińska, Sandra (Polish Journal of Radiology, 2017)
Background : In accordance with the European guidelines on rhinosinusitis and nasal polyps (EPOS 2012), CT is used as the main imaging modality for the assessment intensity of inflammatory lesions. The aim of this study was to measure the differences in the assessment of inflammatory changes in the paranasal sinuses due to different parameters of width (W) and length (L) of the CT window. Material/Methods : A retrospective analysis included 44 CT scans of the paranasal sinuses that were performed in adults. All studies were characterized by the presence of inflammatory changes in at least one of the sinuses. Measurements of the same inflammatory lesions were performed sequentially with different CT windows. The results were statistically analyzed. Results : A statistically significant difference was observed between the average measurements that were performed with the use CT windows dedicated for the sinuses and head. A downward trend in the measured values and a shift towards soft tissue values was observed with decreasing window parameters. Conclusions : A major cause of inaccurate examinations of pathological changes in the paranasal sinuses may be due to selection of unsuitable CT windows. Therefore, in order to avoid missing inflammatory lesions in the paranasal sinuses, it is reasonable to use CT windows dedicated for the sinuses or bones.